Feasibility Assessment of Energy As A Service With Third Party Ownership For Development of Utility-Scale Solar PV In The Consumer Goods Industry - Puspadimiati, Winda; Purwanto, Widodo W (CSID Journal of Infrastructure Development, 2025)
Global awareness of climate change impacts has compelled the power sector to adopt renewable energy as a primary source of electricity, driving innovation in renewable energy business models. This study analyzes the feasibility of Energy as a Service (EaaS) with a Third-Party Ownership (TPO) scheme for utility-scale solar photovoltaic (PV) development in the fast-moving consumer goods (FMCG) industry. Four scenarios of utility-scale solar PV configurations under the EaaS model are evaluated: on-grid ground-mounted (OG-GM), hybrid ground-mounted (H-GM), on-grid floating (OG-F), and hybrid floating (H-F). All scenarios are developed under the assumption of utilizing the PLN grid through a power wheeling lease agreement. The optimal capacity for each scenario is determined using HOMER Pro, followed by an economic analysis to identify the most viable configuration. The results indicate that both on-grid and hybrid configurations can support the consumer’s objective of achieving 100% renewable energy usage. Among the evaluated scenarios, on-grid floating solar PV emerges as the most viable option, providing benefits for both consumers and EaaS providers, including potential electricity cost savings of 16% and avoided emissions of up to 41,299 tons of CO₂ per year. To fully achieve 100% renewable energy consumption, consumers must transition to hybrid configurations, enabling an emission-free electricity system and eliminating the need for Renewable Energy Certificate (REC) purchases. This transition can generate potential annual savings of USD 40,590.96, although it results in an increase in electricity costs of up to 117% due to the integration of battery energy storage systems without grid support. Overall, the implementation of the EaaS TPO model offers mutual benefits for both consumers and energy service companies and can serve as a catalyst for accelerating renewable energy deployment in Indonesia.